A Review of Evolution and Challenges in Corporate Governance - Mohanty, B. K. (Prabandhan: Indian Journal of Management, 2010)
The subject of corporate governance has come to the limelight after the collapses of the high profile companies. Enron, the Texas based energy giant and Worldcom, the telephone giant, shocked the business world for their unethical and illegal operations. Large and trusted companies from Parmalat in Italy and the multinational newspaper group Hollinger revealed significant and deep rooted problems in their corporate governance. Even the director of New York stock exchange, Dick Grasso has been removed from his prestigious post for the non-compliance of the corporate governance practices judiciously before the public. Corporate governance has, of course, been an important field of query within the finance discipline for decades. Researchers in finance have actively investigated the topic for at least a quarter century.